Penerapan Metode Penemuan Terbimbing Untuk Meningkatkan Pemahaman Konsep Dan Kemampuan Penalaran Matematik Siswa Sekolah Dasar - Mimi Hariyani (Kutubkhanah, 2012)
This research was a quasi-experimental designed with pretest-postest without randomized control groups. The research was conducted in March through April 2010 with 92 students in fifth grade of SDN in Gugus 1 District IV Koto Rokan Hulu. The instruments used in this research consisted of testing the understanding of mathematical concepts and reasoning skills, students’attitudes questionnaires, observation sheet, and interview guides. Data analysis was performed by t-test. The results showed that learning mathematics with guided discovery methods can improve understanding of the concepts and mathematical reasoning abilities of students from elementary school. There is a difference in increasing the understanding of concepts and mathematical reasoning ability between students who learned using the method of guided discovery learning with students receiving conventional. Students in the class of guided discovery has increased the understanding of mathematical concepts and reasoning skills higher than students in conventionalclasses